Caregiving Burden Among Family Members Of People With Mental Illness - Bhandari, A.R.; Marahatta, K.; Rana, M.; Ojha, S.P.; Regmi, M.P. (Journal of Psychiatrists' Association of Nepal, 2017)
Background: Presence of a person with mental disorder in family is often associated with some objective and subjective burden on family members, especially those who have a caregiving role. The present study aimed to assess the levels of caregiving burden among family members of people with mental illness. Method: This is a descriptive cross-sectional study in a sample of 56 family caregivers of people with mental illness. Sample was selected using purposive sampling method and their caregiving experience was assessed by using Burden Assessment Schedule. Result: Among the 56 caregivers, 48.2 % had moderate level of burden and 32.1% had severe level of burden. Highly significant difference was observed in the distribution of burden according to level of burden but no significant gender difference was found in the distribution of burden in total and in different domains of BAS. Highly significant burden was found among married and spouse caregivers. Conclusion: As moderate to severe level of caregiving burden was reported by the family caregivers, it is recommended that family intervention should focus on strengthening coping behaviors and social support system to manage caregiving stress.